2022
DOI: 10.1029/2022je007312
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Temperatures and Column Dust Opacities Measured by ExoMars TGO‐ACS‐TIRVIM During the MY34 Global Dust Storm

Abstract: The ExoMars Trace Gas Orbiter (TGO) reached its final orbit around Mars in April 2018. It carries the Atmospheric Chemistry Suite (ACS), which comprises three infrared spectrometers covering different wavelength ranges (Korablev et al., 2018). The thermal infrared spectrometer TIRVIM was designed to continuously monitor the atmospheric column in nadir, while the near-and mid-infrared channels NIR and MIR (and occasionally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
(142 reference statements)
0
7
0
Order By: Relevance
“…The assimilation behaves well and is generally stable, more so than earlier work using TGO observations (Young et al, 2022). This is for two reasons.…”
Section: Assimilation Of Hemispheric Observationsmentioning
confidence: 66%
See 3 more Smart Citations
“…The assimilation behaves well and is generally stable, more so than earlier work using TGO observations (Young et al, 2022). This is for two reasons.…”
Section: Assimilation Of Hemispheric Observationsmentioning
confidence: 66%
“…We exclude dust observations from the assimilation, as EMIRS dust retrievals were not yet available when we ran the assimilation. Young et al (2022) found that assimilating the dust column produces a more accurate assimilation than TuTD during dusty periods, but our L s range is the least dusty part of the year, so we do not expect this to significantly impact our results.…”
Section: Model and Assimilationmentioning
confidence: 76%
See 2 more Smart Citations
“…The quantitative impact of these forcings on the tides' phase structure remains to be further investigated in future studies. Note that data assimilation of TIRVIM temperature and dust retrievals in the Mars PCM does not produce an upward‐propagating phase at southern mid‐latitudes (see Figure 19 in Young et al., 2022): this might be because about half of TIRVIM vertical profiles were not included in the assimilation for p < 5 Pa (due to their lower information content). An assimilation including water ice cloud observations would also further improve the analysis.…”
Section: Thermal Structure and Tides During The Global Dust Eventmentioning
confidence: 99%